The welfare state, an impediment to integration? - Uwe Walz; Dietmar Wellisch (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
We investigate the consequences of redistribution policy on migration and trade in a Standard two-good Heckscher-Ohlin framework. With free trade and factor price equalization, abolishing migration barriers is redundant. With the introduction of government activity, matters change drastically. Redistributive policies create an incentive to migrate in the country providing higher transfers. We show that in such a world, free migration increases the bürden of the welfare program in the rieh country and causes suboptimal national redistribution policies in both countries. It is definitively in the interest of the rieh country to stop short of a relaxation of migration barriers. Rather, a pure free trade regime without migration proves to be preferable.
Keywords: F11; F15; F22; H55; 330; Trade; Migration; Integration; Redistribution Policy; Freihandelszone; Internationale Wanderung; Außenwirtschaftstheorie; Faktorproportionentheorem; Einkommensumverteilung; Sozialstaat; Wohlfahrtsanalyse; Theorie; NAFTA-Staaten